Detecting CMT-BSHM OJT Performance Levels and Issues Affecting Performance: The Foundation for Competency Enhancement Program - Penelope Garcia Colisao (CV. Rayyan Dwi Bharata, 2023)
A mixed method design was used in this study to collect and analyze both quantitative and qualitative data within the same study. using a self-created survey questionnaire The findings:1.Zamboanguenos were the most common tribe among respondents, followed by Visayans and Tausugs, with the majority being females from middle-class families. 2. There were disparities in performance assessments between supervisors and students, particularly in terms of personality development. Supervisors rated the performance as moderate, while students thought it was excellent. 3. There is no significant difference in perceptions of the issues raised affecting work performance between the supervising agencies and the BSHRM OJT practicumers themselves.Â 4.There is no statistically significant relationship between BSHM OJT performance and the problems and issues raised by them, as perceived by practicumers and supervisors in general. The following suggestion would be beneficial to this study: This study should focus on Region IX SUCs, specifically Hospitality and Tourism Business, including Entrepreneurship programs, to determine if females are more likely to enroll. CMT professors should adapt the research to develop a Competency Enhancement Program that focuses on psycho-social dimensions of CMT-BSHM OJT practicumers' academic performance and workplace behavior. A regular stakeholders' forum on business and tourism programs and a benchmarking on best practices on the OJT deployment system can help bridge the gap between competency skills earned and industry-specific skills demanded.